IMPROVING CHILDREN’S BEHAVIOUR ON CLEAN AND HEALTHY LIVING THROUGH AN EDUCATION-BASED LITERACY CORNER - Wahyuni Tri Lestari; Andri Setya Wahyudi; Candra Panji Asmoro; Norfadzilah Binti Ahmad; Fitri Nur Annasu Matin; Fitriana Fitriana (Universitas Airlangga, 2026)
Introduction: Orphanages represent institutional care settings where children are vulnerable to health problems due to inadequate Clean and Healthy Living Behaviors (CHLB), potentially leading to respiratory infections, diarrhea, tuberculosis, anemia, ascariasis, and dental caries. This community empowerment program aimed to improve children’s knowledge, attitudes, and practices related to CHLB through the implementation of an educative literacy corner combined with interactive health education. Methods: This community service involved 25 children at Baabur Rahmah Orphanage, Sidoarjo, conducted from July to October 2025. The program consisted of setting up a literacy corner integrated with interactive health education sessions delivered in four structured phases. The changes of knowledge, attitude, and practice regarding CHLB in children were measured using structured questionnaires before and after community service. Data were analyzed using the Wilcoxon signed-rank test to evaluate effect the program. Results: The educative literacy corner combined with health education significantly improved children’s knowledge (p = 0.000), attitudes (p = 0.008), and practices (p = 0.000) related to CHLB. Conclusion: The combination of an educative literacy corner and interactive health education is an effective strategy to improve children’s knowledge, attitude, and practice of CHLB. This community service provides a sustainable approach to promoting healthy behaviors while simultaneously fostering literacy culture among children in institutional care settings. KEYWORDS children; cleanliness; education; health; literacy corner